Revisión taxonómica de Salvia sección Sigmoideae (Lamiaceae) - Espejo Serna, Adolfo; Ramamoorthy, T.P. (Instituto de Ecología, A.C., 1993)
Salvia section Sigmoideae Epling is revised. The section is composed of 11 species, all endemic to México and recognized by the sigmoid inferior stigmatic branch. The section is divided into two subsections, Cymulosae subsect. nov. and Sigmoideae,  according to the type of infiorescence presented. Salvia  ramamoorthyana Espejo is described as new to Science.